Population ecology: group living and hungry lions. - Coulson, T (2007)
Ecologists have necessarily had to simplify matters in looking at predatorprey dynamics. Study of a situation in which predator and prey live in groups reveals that a key process was previously overlooked. ©2007 Nature Publishing Group.